PTU-113 Quality of life in patients with ileoanal pouch: a survey comparing two different patient populations. (28th May 2012) - Jaboli, M F; Cronin, E; Marelli, L; Gionchetti, P; Rizzello, F; Calafiore, A; Olagunju, O; Poggioli, G; Erian, G; Epstein, O; Hamilton, M; Murray, C
Abstract : Introduction: Ileal pouch anal anastomosis (IPAA) is the standard restorative procedure for ulcerative colitis (UC) following colectomy. This operation is, however, associated with distinct rates of failure and complications. We performed a survey to evaluate the quality of life (QoL) after IPAA comparing patients followed up in two different teaching Hospitals in London (L), UK and Bologna (B), Italy. Methods: A total of 126 (71L+55B) UC patients received the questionnaire by mail or during clinic. The questionnaire was done according to the IBDQ and it was designed to assess pouch function, disease-specific adjustment, lifestyle aspects and psychological factors. 85 (43L+42B) patients (67%) returned it (M/F= 46/39; age 41±16 years); average pouch duration was 5–7 years. Results: There was no significant difference between L and B in terms of age, gender, marital status, pouch duration, bowel frequency (median 3–6 motions per day and 1–2 per night), experience of leakage (30% more than once a week) and need of additional surgery (0.05%). In L there were significantly more patients who had at least one episode of pouchitis (72%) compared to B (33%). L used significantly more alternative remedies (L 11% vs B 0%), antimotility drugs (L 44% vs B 30%), antibiotics (L 65% vs B 29%) and steroids (L 16% vs B 7%). No difference in immunosuppressant (18%) and VSL#3 use (22%). L patients regret having IPAA significantly more frequently (L 13% vs B 0.02%), cope less with the stoma (in L 39% hated it vs 0% in B), suffer more of unpredictability (L 51% vs B 19%), are less capable to hold the stool for more than 1 h (L 62% vs B 88%) and have more worrying thoughts (L 30% vs B 9%). B patients play sport significantly more frequently (B 76% vs L 53%). L and B reported similar QoL, well being, cheerfulness, ability to work, go on holiday and enjoy things they used to do; similar confidence in doing whatever they want and level of concern in finding a toilet. Conclusion: Our survey showed that in London patients developed more pouchitis and therefore used more medications. They cope worse with the pouch and regret more having had surgery. Interestingly in Italy patients play more sport, but the overall quality of life was the same. Extent and severity of disease prior to surgery, smoking and association with primary sclerosis cholangitis may play a role in the increase incidence of pouchitis in London, but these data were not available in our anonymous questionnaire. Different biologic behaviour and/or genetic background may contribute in this difference. Competing interests: None declared.